Some aspects of controllability for non-linear parabolic and hyperbolic equations - Nuñez Chávez, Miguel Roberto (2018)
Descargue el texto completo en el repositorio institucional de la Universidad Federal Fluminense: https://app.uff.br/riuff/handle/1/12750